2013
DOI: 10.1007/s12199-013-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-associated suicide mortality: contrasting roles of climatic warming and the suicide prevention program in Finland

Abstract: Objectives Suicide is a notable cause of death worldwide, and while suicidal behavior appears to be associated with variations in temperature, no estimations are available of climate change impacts on suicide rates. The study aims to evaluate the influence of temperature on suicide mortality, especially on multi-decadal and longer time scales, that is, at scales on which the ongoing warming distinctly operates and is correspondingly appropriate for the current policy responses to warming climate. Methods Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…In our earlier nationwide study from Finland, suicide rate correlated with monthly mean temperature along with global radiation [1], and in another Finnish study, the ambient temperature variation was shown to explain even 60 % of the annual suicide variance in extra-long time series from 1751 to 2008 in Finland [2]. Furthermore, the diurnal temperature variation associated with spring peak of suicides in Helsinki metropolitan area [3].…”
Section: Introductionmentioning
confidence: 81%
“…In our earlier nationwide study from Finland, suicide rate correlated with monthly mean temperature along with global radiation [1], and in another Finnish study, the ambient temperature variation was shown to explain even 60 % of the annual suicide variance in extra-long time series from 1751 to 2008 in Finland [2]. Furthermore, the diurnal temperature variation associated with spring peak of suicides in Helsinki metropolitan area [3].…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, the exceptionally frequent use of clozapine may explain the reduction in the mortality due to suicide taking place since 1984 in Finland. The decreasing trend in suicide mortality is also partly due to a successful suicide prevention program launched in Finland at the population level , in addition to societal changes and better outpatient treatment of mental illness. This major decrease in suicidal deaths has altered the schizophrenia cohort to be more like the general population in terms of cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…The suicide rate is highest early in the course schizophrenia so it may be no coincidence that the reduction in suicide rates in schizophrenia coincides with the roll out of first episode services in Finland. It also coincides with the implementation of a population‐level suicide prevention programme across Finland . These healthcare and population‐level interventions could explain the reduction in suicide rates in schizophrenia.…”
mentioning
confidence: 61%